CSR & Earnings Management: An Assessment of Firm Ethics - Hajawiyah, Ain; Siti Pratiwi, Indriati; Ramadhini, Annisa; Shauki, Elvia; Diyanty, Vera (KnE Social Sciences, 2020)
Purpose - This study aims to examine the effect of CSR disclosure on earnings management practices stated in accrual earnings management, real earnings management, and in aggregate practice (accrual and real). Design/methodology/approach - Assisted with NVivo 12 Pro software, this quantitative study measures CSR disclosures of 186 annual reports made by 62 manufacturing firms listed on the Indonesia Stock Exchange (IDX) in the period between 2013 and 2015. Period coverage of 2013-2015 is chosen to keep consistency of applied regulation about CSR disclosure in Indonesia. The data are analyzed using multiple linear regression. Findings - This study finds that firms with high CSR disclosures would have low levels of accrual and aggregate earnings management. There is no significant effect of CSR disclosure to real earnings management practice. Research limitations/implications - The results of this study may provide additional literature to examine the effect of CSR disclosure on the practice of comprehensive earnings management (accrual and real). Data to measure real earnings management practices is not entirely available. There is a high chance of subjectivity in measuring the level of CSR disclosure. Practical implications - For company, it can provide information regarding the importance of CSR disclosure. For regulators, it can be a consideration to make strict rules related to CSR disclosure. Originality/value - This study provide a comprehensive picture by examining the effect of CSR disclosure on all types of earnings management by the firm. Keywords: CSR disclosure, real earnings management, accrual earnings management